Função ventricular esquerda e respostas cardiorrespiratórias após reabilitação cardíaca hospitalar em pacientes submetidos à cirurgia de revascularização do miocárdio - Mendes, Renata Gonçalves (2008)
It is well-known that cardiac autonomic and pulmonary function are impaired after coronary artery bypass surgery (CABG). Strategies resulting in beneficial cardiorespiratory responses as soon as possible after surgery are clinically important in these patients. However, information on the differences in cardiorespiratory responses of these patients to inpatient cardiac rehabilitation (CR) with distinct left ventricular (LVF) is still scant. Therefore, the purpose of this study was to assess the cardiorespiratory responses to a short-term inpatient CR programme in patients with LVF normal and reduced. Twenty three patients were studied and divided into LVF normal group (LVFN, n=12) or reduced group (LVFR, n=11). Cardiac autonomic function was evaluated by heart rate variability (HRV) and the pulmonary function by spirometric and respiratory muscle strength (RMS) at (1) post-operative day 1 (PO1) and (2) day before discharge. Heart rate (HR) and R-R intervals (R-Ri) were recorded by telemetry system Polar S810i, at rest, in supine and sitting position. HRV was evaluated in time domain by mean R-R (mean R-R), square root of the mean squared differences of successive R-Ri (RMSSD) and standard deviation of all R-Ri (SDNN) indexes (ms) The spirometric data of vital capacity (VC), forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1) and maximal voluntary ventilation (MVV) were obtained and the RMS was measured indirectly by maximal inspiratory (MIP) and expiratory (MEP) pressures. All patients initiated the CR on PO1 following a programme of progressive steps composed of whole body and breathing exercises previously established until discharge. Results: After inpatient CR, both groups presented improvement of mean R-R (ms) and RMSSD (ms) indexes at rest and beneficial response to postural change with lower RMSSD (ms) index in sitting position. Significant improvement of pulmonary function in both groups was observed to majority spirometric data as FVC, MVV and FEV1 and RMS only presented tend to improvement in response to CR programme Conclusions: These results indicate that patients undergoing CABG with preserved or depressed LVF presented beneficial cardiorespiratory responses to CR after surgery. We also assign slightly more favourable responses on autonomic function in those with depressed LVF without additional risks. Therefore, the inpatient whole CR should be strongly indicates as soon as possible post-CABG even in patients with cardiac dysfunction. Financial support: CNPq e FAPESP (05/59427-7).